2020
DOI: 10.33448/rsd-v9i4.2811
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem matemática da cinética de secagem em camada de espuma da folha da gravioleira (Annona muricata Linn) e caracterização do pó obtido

Abstract: 1 Modelagem matemática da cinética de secagem em camada de espuma da folha da gravioleira (Annona muricata Linn) e caracterização do pó obtido Mathematical modeling of drying kinetics in foam-mat drying of soursop (Annona muricata Linn) leaf and Characterization of the obtained powder Modelado matemático de cinética de secado de la capa de espuma de la hoja de guanábana (Annona muricata Linn) y caracterización del povo obtenido 2 Resumo A graviola (Annona muricata L.) vem se destacando pelas diferentes atribui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Experiment 2 (376.78%) showed the lowest mean expansion percentage, where the stirring time used was the top level of the planning and the foaming concentration was the minimum. Oliveira et al (2020) also observed that lower foam densities lead to greater air incorporation and retention, and, consequently, greater foam expansion.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Experiment 2 (376.78%) showed the lowest mean expansion percentage, where the stirring time used was the top level of the planning and the foaming concentration was the minimum. Oliveira et al (2020) also observed that lower foam densities lead to greater air incorporation and retention, and, consequently, greater foam expansion.…”
Section: Resultsmentioning
confidence: 79%
“…The complete factorial experimental design was used to evaluate the efficiency of the foam layer drying process of Mentha crispa, in order to verify significant effects of the input variables on the response variables. The definition of the independent variables of the process was based on studies of the foam drying of the blackberry leaf (SILVA, 2019), soursop leaf (OLIVEIRA et al, 2020) and the inner bark of juazeiro (MOREIRA et al, 2021). The assessed planning matrix verified the influences of the input variables: stirring time for foam production, percentage concentration of foaming agent and drying temperature; on the response variables: drying time and final water content.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As espumas que não desestabilizam ou colapsam por pelo menos uma hora, são as mais indicadas para o processo de secagem (Brygidyr, Rzepecka & Mcconnell, 1977;Ratti & Kudra, 2006). No estudo de Oliveira et al, (2020) foram observados o desprendimento de volume da espuma da folha da graviola de 2,5 mL, 2,6 mL e 4,4 mL para as condições mínimas, centrais e máximas do planejamento em 60 minutos, respectivamente. De modo geral, pode-se considerar o resultado de estabilidade da espuma do Ziziphus joazeiro satisfatório, visto que o maior volume drenado foi de 5,5 mL nas condições mínimas do planejamento.…”
Section: Estabilidadeunclassified